Splenic injury associated with colonoscopy in hospitalized patients: Incidence, risk factors, management, and outcome - Koop, Herbert; Skupnik, Christoph; Schnoor, Torsten; Horenkamp-Sonntag, Dirk (Endoscopy International Open, 2024)
Background and study aims The frequency of splenic injuries due to coloscopy is largely unknown. Therefore, the aim of this study was to give estimate the risk for hospitalized patients.Patients and methods Using the administrative database from a health insurance company with more than 10 million insured subjects, patients undergoing inpatient colonoscopy associated with a splenic injury within 2 weeks were retrieved from the administrative records based upon OPS (comparable to International Classification of Procedures in Medicine) and ICD-10 codes. In each case identified (n = 141), the individual course of the hospital stay was reconstructed and analyzed by two experienced physicians. Patients with overt other causes of splenic injuries (e. g. abominal surgery, trauma etc.) were not further evaluated.Results Among 190,927 total colonoscopies over a 5-year period, 27 splenic lesions were most likely solely due to colonoscopy. This accounts for 14.1 splenic injuries per 100,000 colonoscopies or one lesion in 7,071 patients. Afflicted patients were older and more likely to be female than male (risk in females: 1 in 5,324 colonoscopies). Surgical interventions were carried out in 17 cases, predominantly splenectomy (n = 15) whereas 10 events were managed conservatively. Transfusions and requirement for intensive care unit treatment were strong predictors of need for surgery. Most lesions (74%) were diagnosed within 48 hours after colonoscopy. Death occurred in two patients, but less likely directly due to the splenic injury.Conclusions Administrative data analysis suggests that splenic injuries due to colonoscopy are more frequent than previously estimated. Endoscopists should be aware of this rare life-threatening adverse event.
Keywords: Quality and logistical aspects; Performance and complications; Epidemiology; Pediatric endoscopy